Do better political institutions help in reducing political pressure on state-owned banks? Evidence from developing countries - Badar Nadeem Ashraf; Sidra Arshad; Liang Yan (Journal of Risk and Financial Management, 2018)
This study examines whether state-owned banks face political pressure and whether the improvement in political institutions alleviates this pressure. The theory of political benefits argues that politicians use state-owned banks for political purposes such as obtaining and maintaining political support. We reviewed extant empirical research and found that the existing evidence is mixed; some studies support while others reject the theory. In this backdrop, we analyzed a sample of 185 state-owned banks from 51 developing countries over the period 1998-2012 and provide renewed evidence supporting the theory. Specifically, we found that state-owned banks face significant political pressure in developing countries; that is, they lend more and earn less in election years. Next, we observed that the political pressure is prevalent only in the countries with weak political institutions. Strong political institutions in the form of higher constraints on policy change decisions of incumbent government and higher democratic accountability are helpful in eliminating political pressure on state-owned banks in developing countries.
Keywords: G18; G21; G28; P16; 330; political institutions; state-owned banks; elections; political pressure; bank lending; bank profitability